The Principle of Non Discrimination Against the Unilateral Determination of Payment Method Provisions in Non Cash Buying and Selling Transactions - Alizcia Dora Parhusip; Iwan Erar Joesoef (PALAR | PAKUAN LAW REVIEW, 2026)
This study aims to identify how sales and purchase transactions can justice fairness for consumers to avoid discrimination in payment methods. The research employs a normative juridical method with statutory, case, and conceptual approaches. The legal materials used consist of primary, secondary, and tertiary sources, analyzed qualitatively by interpreting data obtained from both literature studies and interviews to answer questions regarding the application of legal principles and legislation in consumer protection. This study discusses the application of the principle of non-discrimination in the practice of rejecting cash payments by business actors, with a case study at RUDS Coffee, which implements a cashless-only payment system. The results indicate that such a policy potentially violates the provisions of Law Number 7 of 2011 on Currency and Law Number 8 of 1999 on Consumer Protection, as it limits consumers’ rights to use Rupiah in cash as legal tender. The refusal to accept cash payments without a valid reason constitutes a form of discrimination against consumers who lack access to digital financial services. Therefore, strengthening regulations and supervision of the payment system is necessary to ensure legal certainty, fairness, and equal protection for all consumers. Key Words: Consumer Protection, Cash Payment Refusal, Legal Certainty, Sales and Purchase Transactions.